Efficient Flexible Perovskite Solar Cells with Reduced Hysteresis Employing Cobalt Nitrate Treated SnO2. Issue 7 (29th April 2022) - Wu, Donghui; Ai, Zhenhai; Li, Sheng; Chen, Junjun; Zhao, Yue; Ma, Tianshu; Wang, Huayang; Wang, Changlei; Li, Xiaofeng
Abstract : Flexible perovskite solar cells (PSCs) have great potential for portable electronics, however, suffer from large hysteresis in regular structure. Insufficient charge extraction in commonly used tin dioxide (SnO2 ) electron transporting layer (ETL) is regarded as one possible origin of hysteresis due to the low crystallinity and energy level mismatching. Here, the hysteresis of flexible PSCs is suppressed by synthesizing cobalt‐modified SnO2 ETLs, which improve electron extraction capability due to the high carrier mobility and well‐aligned energy levels. Moreover, cobalt modification passivates the defects on the ETL surface, facilitates sequential perovskite film growth, and inhibits carrier recombination. As a result, flexible PSCs with efficiencies exceeding 20% are obtained with significantly reduced hysteresis and enhanced illumination stability. Comprehensive optoelectronic simulations are conducted to unveil the deep mechanisms of eliminated hysteresis. The proposed work provides an efficient and facile strategy for the fabrication of high‐performance flexible PSCs upon future commercialization. Abstract : Cobalt modulation of SnO2 electron transporting layer (ETL) significantly improves the performance and reduces the hysteresis of flexible perovskite solar cells (PSCs). Cobalt nitrate improves the crystallinity of SnO2 nanoparticles, reduces surface defects of ETL and facilitates perovskite film growth, leads to hysteresis‐less flexible PSCs with efficiencies over 20% in regular structure.